The Efforts to Improve Learning Focus of Hyperactive Children Through Directed Motor Activities - Jenal Abidin; Rita Susilawati; Elsa Meilani; Rini Fitriyani (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
This research is motivated by the low learning focus of hyperactive children at RA Al-Bayan Parigi Pangandaran. Hyperactive children tend to have difficulty concentrating, are easily distracted, and exhibit excessive motor activity that disrupts the learning process. This study aims to improve children's learning focus through structured motor activities. The research method used is Classroom Action Research (CAR) with the Kemmis and McTaggart model consisting of two cycles. The research subjects were group A children totaling 29 people. Data collection techniques used observation, documentation, and performance assessment. The results of the study showed an increase in children's learning focus from the pre-cycle of 48.27%, to 83.35% in cycle I, and reaching 93.09% in cycle II. This indicates that structured motor activities are effective in improving the learning focus of hyperactive children.